Optimization of Main Ingredient Ratio, Metabolomics Analysis, and Antioxidant Activity Analysis of Lycopene-Enriched Compound Fruit Wine - Kunyi Liu; Xiangyu Liu; Teng Wang; Qi Wang; Lei Feng; Rui Su; Meng Zhang; Bin Xu; Fei Chen; Pingping Li (Fermentation, 2023)
To find the optimal main ingredient ratio of compound fruit wine for enriching the varieties of lycopene-enriched fruit products and improving their economic value, fuzzy mathematics sensory evaluation and the D-optimal mixture design were considered. Under the main ingredient ratios of tomato juice, papaya juice, carrot juice, and gac fruit juice of 27.2%, 27.5%, 10.0%, and 35.3%, respectively, a clear and transparent compound fruit wine with a full-bodied fruit and wine aroma and mellow taste can be obtained. Meanwhile, a total of 406 metabolites were identified in the compound fruit wine, which were classified into nine superclasses including lipids and lipid-like molecules (150), organic acids and derivatives (69), and others. The relative levels of 54 metabolites after optimization were decreased significantly (VIP > 1.0, p < 0.05, FC < 0.5), while the relative levels of 106 metabolites including lycopene and (13Z)-lycopene were increased significantly (VIP > 1.0, p < 0.05, FC > 2). Furthermore, the EC50 values of this compound fruit wine after optimization of the main ingredient ratio for scavenging ABTS+·, DPPH·, O2−·, and ·OH were 78.62%, 57.74%, 42.85%, and 59.91%, respectively. Together, a compound fruit wine rich in lycopene with antioxidant activities was manufactured, which has application potential in the development of functional foods.